1983
DOI: 10.1136/adc.58.12.1022
|View full text |Cite
|
Sign up to set email alerts
|

Haemangioma with thrombocytopenia (Kasabach-Merritt syndrome).

Abstract: that in the long term and on the basis of the radiographic evidence our patient's bone structure may be normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is recommended as emergency treatment to alleviate hazardous coagulopathies and life‐ or function‐threatening hemangiomas 2,8,18,19. The failure of other therapies particularly steroids is a further indication 9,20.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended as emergency treatment to alleviate hazardous coagulopathies and life‐ or function‐threatening hemangiomas 2,8,18,19. The failure of other therapies particularly steroids is a further indication 9,20.…”
Section: Discussionmentioning
confidence: 99%
“…It has been concluded that in patients not responding to corticosteroids, alternative therapies (e.g. radiotherapy and/or interferon alpha) should be used within 3-4 weeks [30].…”
Section: Steroidsmentioning
confidence: 99%